Determination Of Phytoncidal Activity Of Plants - M.R. Kushbakova; M.Sh. Usmanova (Zien Journals, 2024)
Modern technical means are unable to provide a healthy air environment. On the contrary, indoor air conditioners are often sources of increased microbial contamination. At the same time, volatile secretions of many plants are able to effectively suppress the vital activity of microorganisms. The relevance of the work is to find environmentally safe and effective means of improving the air environment. To do this, it is necessary to study the phytoncidal activity of plants. An experiment was conducted to check which plant species produce more phytoncides. The practical significance of the work is determined by the possibility of using the results obtained to improve the composition of the air around us. Plants with high phytoncidal activity should be used in landscaping of residential premises and urban areas
Keywords: Phytoncide activity; vitamin-like substances; atmospheric vitamins